Evaluating the usefulness of Eye Tracking in Game-based Learning - Kristian Kiili; Harri Ketamo; Michael D. Kickmeier-Rust (Serious Games Society, 2014)
The challenge of educational game design is to develop solutions that please as many players as possible, but are still educationally effective. How learning happens in games is methodologically very challenging to point out and thus it is usually avoided. In this paper we tackle this challenge with eye tracking method. The aim of this research is to study the meaning of cognitive feedback in educational games and evaluate the usefulness of eye tracking method in game based learning research and game design. Based on perceptual data we evaluated the playing behavior of 43 Finnish and Austrian children aged from 7 to 16. Four different games were used as test-beds. The results indicated that players' perception patterns varied a lot and some players even missed relevant information during playing. The results showed that extraneous elements should be eliminated from the game world in order to avoid incidental processing in crucial moments. Animated content easily grasps player's attention, which may disturb learning activities. Especially low performers and inattentive players have difficulties in distinguishing important and irrelevant content and tend to stick to salient elements no matter of their importance for a task. However, it is not reasonable to exclude all extraneous elements because it decreases engagement and immersion. Thus, balancing of extraneous and crucial elements is essential. Overall, the results showed that eye tracking can provide important information from game based learning process and game designs. However, we have to be careful when interpreting the perceptual data, because we cannot be sure if the player understands everything that he or she is paying attention to. Thus, eye tracking should be complemented with offline methods like retrospective interview that was successfully used in this research.